Washback in EFL Writing Courses: A Reflective Teaching at English Education Study Program of Teacher Training and Education Faculty of Universitas Maritim Raja Ali Haji - Nopita, Dewi (Journal of Language Learning and Research (JOLLAR), 2019)
Washback is one of the principles of language assessment. It is the effects of an assessment on teaching and learning prior to the assessment itself, that is, on preparation for the assessment (Brown, 2004). This article aims at describing washback in EFL writing courses at English study program of teacher training and education faculty of Universitas Maritim Raja Ali Haji (UMRAH). The description was got from my own experiences and another writing lecturer?s. To get a more detail description from another lecturer, I interviewed him and his students dealing with the assessment done during the course as well as its impact towards the teaching and learning. Futhermore, I did observation on the improvement of the students? task and test scores. Finally, it was found that in writing courses at English Education Study Program of Teacher training and Education Faculty (FKIP) of UMRAH, washback did contribute to the quality of teaching and learning since it provides feedback for both the instructors and the students. The feedback helps the instructors to plan a better teaching as well as helps students to do a better learning. The form, content, focus and delivery of writing assessments (tasks and tests) administered during the course determine the way it is taught and the way the students learn. As a result, these features in turn tend to affect the success of the course.